KETERLIBATAN KYAI DALAM POLITIK (STUDI ANALISIS PERAN KH. MUH MUSTAMSIKIN DALAM PEMERINTAHAN DAERAH KABUPATEN KENDAL) - SOLKHAH MUFRIKHAH, SOLKHAH MUFRIKHAH (Politika: Jurnal Ilmu Politik, 2014)
The involvement of kyai be described in the domain of politics is interesting because in almost every general election, the involvement of kyai absolutely necessary as a tool to gain sound. As the development of the, involvement in the domain kyai in fact also not just limited to the role behind the screen, but perform as candidates deputy head of the head of the regions and regions. One of them is the phenomenon kyai involvement in the district administration of Kendal, Central Java. The results of election districts kendal last year which produce a victory for a couple Widya Kandi Susanti-KH. Muh Mustamsikin interesting to be described, especially regarding the role of KH. Muh Mustamsikin who have a background as kyai. From the research, the involvement of KH. Muh. Mustamsikin in local government districts of Kendal supported by a desire to to enter into the system is to be involved active set the course of government. KH. Muh. Mustamsikin make use of social capital that owned a very effective in banged voters .In view of personal as kyai who actively involved in politics, KH.Muh Mustamsikin having ideals that will advance all of something that smells of religion in the concept of the development .Just this desire has become a blunder for kh .Muh mustamsikin kh themselves because. Muh mustamsikin be out of PKB due to conflicts of interest with NU. In addition, was not political agreement with regent Widya Kandi Susanti caused KH. Muh Mustamsikin areas that have clearly decided to participate in a public policy. This is what causing dissension between them. The keywords: kyai in politics, local governments.